Persuasive Intelligence and Its Relationship to Mindfulness Among Kindergarten Teachers - Abdulhameed, Hind Luay (Journal of Educational and Psychological Sciences, 2025)
This correlational-descriptive applied research aimed to identify the level of persuasive intelligence and mindfulness among kindergarten teachers in Baghdad/Al-Rusafa Al-Thaniya Education Directorate, and the correlational relationship between them. To achieve the study objectives, the researcher developed a Persuasive Intelligence Scale (30 items) and adopted the Mindfulness Scale (Amer, 2016) (31 cognitive mindfulness items). Both instruments' characteristics were confirmed and applied to a simple random sample of (200) kindergarten teachers during the 2024-2025 academic year. The results indicated that the teachers have a moderate level of persuasive intelligence and moderate mindfulness, and there is a statistically significant positive correlation between persuasive intelligence and mindfulness among kindergarten teachers. The researcher recommended: focusing on mindfulness as an important educational topic for all age groups; emphasizing scientific fields that focus on intelligence processes to reach higher levels; prioritizing cognitive and psychological activities that help develop mindfulness inside and outside the university; and necessity of developing and effectively employing programs addressing mindfulness for better future outcomes.
Keywords: Persuasive intelligence; mindfulness; kindergarten teachers